(untitled) (قضايا سياسية, 2025)
Globalization, by means of its tools represented by technological advancements in communication, information, media, and digital technologies linking science, technology, and culture consistent with global dimensions, as well as the globalization of democratic political systems, has introduced new developments and actors that have transformed contemporary life. These developments have created a networked, borderless, fast-paced, pervasive, and enticing communicative environment that transcends national boundaries toward global. Consequently, societies with cyber-virtual dimensions have emerged parallel to local communities. These cyber societies are characterized by their impartiality to closed political, social, and affiliative domestic laws, while simultaneously being influenced by temporal, spatial, geographical, and historical contexts. They have also redefined the logic of communication and human relationships, ultimately altering individuals’ sources of identity. Due to the integration of these cyber societies with the realities of local communities shaped by individuals’ psychological states and their attempts to escape the complexities of kinship-based social relations and the authoritarian politics of the political community in pursuit of a better life along with the flexible and dynamic nature of identity, the position of individual belonging has shifted. Individuals have redefined their presence and self-conception by reconstructing their old identities and forming cyber identities with specific characteristics, either in conflict with or in harmony with traditional identities. Without neglecting the contradictions accompanying this complex and comprehensive process, the rebuilding of identity in light of the variables of globalization has undergone and continues to undergo various interactive processes across different cultural, social, political, and economic levels.